FINANCIAL RESILIENCE: LESSONS FROM GLOBAL CRISES - Rahmatullaeva Lobarkhon, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Financial resilience is defined as the structural and strategic components of an organization that enable it to navigate economic volatility safely and steadily. It involves proactive financial management practices, such as managing debt, diversifying revenue streams, and maintaining cash reserves, to ensure sustainability and success amid external stresses. Better financial resilience reduces the money-related mental health issues that people on low, moderate and volatile incomes often experience.